The usage of thermoelectric generator as a renewable energy source - Cekmas Cekdin; Zainuddin Nawawi; Muhammad Faizal (Universitas Ahmad Dahlan, 2020)
Currently thermoelectric generators (TEG) are widely used in biomedical, military and space satellite power applications. TEG of high power plants are mostly used in automobile and industrial engines. This paper discusses TEG as a renewable energy source. Here the TEG in the application is used in the thermoelectric generator power plant. The working principle of this thermoelectric generator is on the heat side of the TEG peltier which is coated in metal in the form of aluminum, which is heated by a heater. And the cold side of the TEG Peltier is placed on the heat sink (as a heat dissipation metal). Heatsinks are submerged in water which are submerged about half or more. If the temperature of the metal being heated and the temperature of heat dissipation metal have a certain difference, then the temperature difference causes TEG to start working. The greater the temperature difference, the greater the electrical energy produced will be. However, if the temperature difference is too large it will damage the bismuth semiconductor material used. After TEG starts working it will produce voltage and current.